PENDAMPINGAN USAHA STIK DARI EKSTRAK KULIT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) - Fatmawati; Fahmi Yahya; Rini Qurratul Aini; Erma Suryani; Riadi Suhendra (FKIP Universitas Samawa, 2022)
Dragon fruit is an exotic fruit because of its interesting appearance, it tastes sweet acid refreshing and has a variety of benefits for health. Even though the flesh is so nice to consume with a various of benefits. But dragon fruit skin is usually only used as waste and is not utilized. In fact, dragon fruit skin, especially red dragon fruit containing antosinine which can be extracted into a natural food coloring that is safe for the body and is well consumed in the long term. In this activity, we tried to accompany the business of the Faculty of Teacher Training and Education of the University of Samawa who utilized the waste of red dragon fruit skin as raw materials. The product is in the form of stick snacks named Hylo Poly Stick which is packed with attractive packaging. Mentoring was carried out for two months. Activities run smoothly and according to plan. Students managed to run their business and get considerable profits.